Strategi Peningkatan Kualitas Pelayanan Guna Meningkatkan Loyalitas Pelanggan di Sektor Jasa Transportasi Online Gojek - Devyasri Nusa Handayani; Dewi Sri; Danendra Amantha Widhia; Mohamad Zein Saleh (Trending: Jurnal Manajemen dan Ekonomi, 2025)
This research aims to analyze a strategy to improve service quality established by PT Gojek Indonesia to increase customer loyalty. By using a qualitative approach, the results of this research show that strategies for improving technology features can improve user experience and strengthen long-term relationships with customers. Apart from that, it can provide sustainable innovation to maintain existing rivals amidst intense competition in the online transportation services sector, namely Gojek. This research provides direction for companies in developing more effective strategies in improving service quality and building customer loyalty.